Bringing facilitation into view - Elizabeth A. van Es; Miriam Gamoran Sherin (SpringerOpen, 2017)
Abstract The articles in this volume reflect the continued popularity of video in professional development and raise important questions about how to situate video productively in varied contexts. Together, they highlight the complexity of expanding video-based professional development beyond designers and the challenges that designers and facilitators experience as they prepare others to lead teacher learning in these settings. In this commentary, we examine how these papers advance research on facilitation of professional development, with a particular focus on the issues for using video productively with teachers. We conclude by raising several issues for future research.